Incentives and influence activities in the public sector: The trade-off in performance budgeting and conditional grants - Ivo Bischoff; Frédéric Blaeschke (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
Performance budgeting schemes in the public sector have to operate with imperfect performance measures. We argue that these imperfections generate incentives for the potential recipients of performance-based funds to use up resources in socially wasteful influence activities. We develop a game-theoretical model to analyse the trade-off between the efficiency-enhancing effect of performance budgeting and the social waste it induces. Comparing a performance signal based on recipients' effort to a signal based on their output shows that a) the former evokes more social waste while the latter amplifies inequality in the amount of public services across districts. Performance budgeting schemes using the outputbased signal yield welfare gains in a wide range of parameter constellations while the applicability of PB-schemes using the effort-based signal is limited. We also show that welfare losses arise when the government is opportunistic. Our model can be applied to the very similar trade-off emerging with the use of conditional grants in federalist countries.
Keywords: D7; H77; H5; H11; 330; Performance budgeting; rent-seeking; bureaucracy; public-sector production; conditional grants; opportunistic government